The Influence of ESG Disclosure, Leverage, and Company Size on Financial Performance at Bank KBMI 3 and 4: The Role of Credit Quality Moderation - Amirullah, Amirullah; Endri, Endri (International Journal of Social and Management Studies, 2025)
The banking industry is under pressure to integrate sustainability practices while maintaining profitability. This research aims to examine the impact of Environmental, Social, and Governance (ESG) Disclosure, Leverage (Debt-to-Equity Ratio/DER), and firm SIZE (SIZE) on financial performance (Return on Assets/ROA) in publicly-owned banks KBMI 3 and 4 during the period of 2019 ~ 2023, as well as the moderating role of Credit Quality (Non-Performing Loan/NPL). Data from five years across eight banks were analyzed using random and fixed-effects regression. The main results indicate that ESG Disclosure and DER have a significant positive direct effect on ROA, while SIZE has a negative effect. NPL has been proven to strengthen the relationship between ESG-ROA and DER-ROA confirming that good credit risk management enhances the benefits of sustainability strategies and funding but does not moderate the influence of company SIZE. This moderation model demonstrates a strong capacity to account for variation in ROA, highlighting the crucial synergy between ESG practices and credit risk management in enhancing bank performance